SAM, An integrated Pest Control Strategy For Farm-Stored Wheat - Reed, Carl; Herrman, Tim J.; Higgins, Randall; Harner III, Joseph (My University, 1995)
This publication provides information about the sanitation, aeration, monitoring of grains that improves the control of stored-grain insects and helps reduce reliance on pest control chemicals.
MF2113_1995_05
Keywords: MF2113; Equipment and structures; Crops; Insects; MF